PENGARUH MEDIA PENDINGIN TERHADAP SIFAT MEKANIK DAN STRUKTUR MIKRO PLAT BAJA KARBON ASTM A-36 - Sumiyanto, Sumiyanto; Abdunnaser, Abdunnaser (Bina Teknika, 2015)
working. Workmanship of austenisation is done through warm-up of specimen at temperature 9000C during one hour clock, then made cool in coolant giving speed of different refrigeration. As coolant is refrigeration of lag in refrigeration stove in air-gap (air), dye oli, and dye water giving speed of highest refrigeration. Attempt result indicate that strength of steel from material early 423,9 MPa, after diaustenisation specimen, the strength increase becoming 474,9 MPa through air cooling, and 560,5 MPa through refrigeration dye water. Media cooler dye water, yield mechanical property is less good, because specimen manjadi is fragible (small elongation 6%). Microstructure observation becomeed militant, phase which formed is ferrite as matrik and pearlite. Increasing of strength of call is caused by item formed by pearlite is higher distribution from at initial material. Specimen with refrigeration dye water, microstructure type which formed becoming change, phase which formed is ferrite of form of needle as matrik and martensite. This microstructure type give metal become brittle. Although the strength is highest (717,3 MPa).